Can concurrent teaching promote equal biomechanical adaptations at front crawl and backstroke swimming? - Costa, Mário (2017)
Purpose: Analyse the biomechanical adaptations in front crawl and backstroke swimming, as influenced by the implementation of a concurrent teaching programme. Methods: Sixteen participants (19.75±1.13 years) underwent a 30 weeks intervention characterized with an increasing complexity to accomplish motor skills in the following order: (i) lower limbs propulsion; (ii) lower limbs propulsion synchronized with breathing cycle; (iii) lower limbs propulsion synchronized with one upper limb action; (iv) lower limbs propulsion synchronized with both breathing cycle and one upper limb action; (v) full swimming stroke; (vi) motor trajectory of the arms stroke. Performance and biomechanics were measured at front crawl and backstroke during three time points throughout the programme. Results: There were improvements in performance over time at front crawl (21.49s to 19.99s, p < 0.01) and backstroke (27.15s to 24.60s, p = 0.01). Significant improvements were found for velocity at front crawl (1.13m/s to 1.22m/s, p < 0.01) and backstroke (0.92m/s to 1.00m/s, < 0.01). Stroke frequency increased at backstroke (0.64 to 0.73Hz, p = 0.01), while the intra-cyclic variation of the velocity decreased at front crawl (0.13 to 0.12%, p = 0.02). There was also a moderate-high inter-subject variability in response to the programme. Conclusions: These findings support that a programme of 30 weeks teaching concurrently front crawl and backstroke is effective to promote similar biomechanical adaptations in low-tier swimmers. However, each subject shows an individual response to better adapt the biomechanical actions and to reach a higher level of expertise.